Límites entre la memoria y la historia para construir una cátedra por la paz (2020)
The Colombian post-conflict as a pedagogical phenomenon based on the Chair of Peace has once again placed the issue of Violence as a central element in the processes of teaching and learning in schools. But, like other predecessor chairs such as the Chair of Afro-Colombian Studies (CEA), entrepreneurship or sexuality, teachers' concerns are more abundant than the possible ways of facing this challenge in the school setting. This proposal is based on the concern of how to give shape to a chair of peace in a municipality like El Cocuy, which was affected by bipartisan violence in the middle of the last century. This question opens up the possibility of making some reflections that we consider should be taken into account when building a pedagogical proposal focused on teaching the armed conflict in Colombia. Firstly, the contextualization must start from local history; secondly, it must enunciate the theoretical and methodological limits to find places of encounter - disagreements between memory and history; and finally, it will provide an answer to why a pedagogy of memory is necessary.